Abnormal cytoskeletal remodeling but normal neuronal excitability in a mouse model of the recurrent developmental and epileptic encephalopathy-susceptibility KCNB1-p.R312H variant - Alessandro Bortolami; Elena Forzisi Kathera-Ibarra; Anastasia Balatsky; Mansi Dubey; Rusheel Amin; Srinidi Venkateswaran; Stefania Dutto; Ishan Seth; Adam Ashor; Angel Nwandiko; Ping-Yue Pan; David P. Crockett; et al. (Communications Biology)
Abstract Integrin_K+ Channel_Complexes (IKCs), are implicated in neurodevelopment and cause developmental and epileptic encephalopathy (DEE) through mechanisms that were poorly understood. Here, we investigate the function of neocortical IKCs formed by voltage-gated potassium (Kv) channels Kcnb1 and α5β5 integrin dimers in wild-type (WT) and homozygous knock-in (KI) Kcnb1 R312H(+/+) mouse model of DEE. Kcnb1 R312H(+/+) mice suffer from severe cognitive deficit and compulsive behavior. Their brains show neuronal damage in multiple areas and disrupted corticocortical and corticothalamic connectivity along with aberrant glutamatergic vesicular transport. Surprisingly, the electrical properties of Kcnb1 R312H(+/+) pyramidal neurons are similar to those of WT neurons, indicating that the arginine to histidine replacement does not affect the conducting properties of the mutant channel. In contrast, fluorescence recovery after photobleaching, biochemistry, and immunofluorescence, reveal marked differences in the way WT and Kcnb1 R312H(+/+) neurons modulate the remodeling of the actin cytoskeleton, a key player in the processes underlying neurodevelopment. Together these results demonstrate that Kv channels can cause multiple conditions, including epileptic seizures, through mechanisms that do not involve their conducting functions and put forward the idea that the etiology of DEE may be primarily non-ionic.